Characterization and comparison of strains of Pasteurella multocida associated with cases of progressive atrophic rhinitis and porcine pneumonia in Argentina - Bessone, Fernando Anibal (2019)
Pasteurella multocida (Pm) is the causative agent of progressive atrophic rhinitis (PAR) and pneumonicpasteurellosis (PN) in pigs. Pm is a member of the porcine respiratory complex responsible for important economic loss inthe pig industry. This study aimed to characterize the Pm strains recovered from clinical cases of PN and PAR and to elucidate theantibiotic susceptibility profiles of the strains.Materials and Methods: Sixty strains were characterized molecularly by polymerase chain reaction to determine speciesspecific gene, capsular type (A or D), and toxin A production. The agar diffusion method was employed to evaluate antibioticresistance profiles. We found that 65% of strains belonged to capsular type A or D, and 15% of those were positive to toxA gene.The antibiotic susceptibility profiles found were sensitive in decreasing order to: Enrofloxacin, ceftiofur (CTF), ampicillin,tilmicosin (TIL), florfenicol (FFN), spectinomycin (SPC), gentamicin, oxytetracycline (OTC), and trimethoprimsulfamethoxazole (TMS). Strains were resistant in decreasing order to: Lincomycin (LIN), tylosin (TYL), erythromycin(ERY), TMS, SPC, OTC, FFN, TIL, and CTF. The toxA gene was detected in many Pm isolates from pneumonic lungs. Capsule type A or D was the mostfrequently found among the collected isolates. LIN, TYL, and ERY are the drugs which showed higher percentages of resistant isolates.